Conservatism of Islamic Legal Arguments in Granting Marriage Dispensation at the Indonesian Religious Courts - Mhd Yazid (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
This article discusses additional legal arguments used by judges in granting proposals for marriage dispensation at the Religious Courts. The article is based on the fact that many of these cases were granted by judges at the Religious Courts in the midst of child protection initiated by the state through Law no. 16 of 2019. This research discusses additional arguments used by judges in several Religious Courts in Indonesia in considering the best interest for children in marriage dispensation decisions. The data in this article was collected from judges' decisions regarding marriage dispensation in 2022. Using a legal philosophy approach, this article finds that additional arguments are a very decisive part for judges in granting marriage dispensation. In other words, the judge cannot grant a marriage dispensation without additional arguments. Among these arguments are the principles of fiqh, the Qur'an or interpretation, hadith, fiqh, and social conditions.